Quadriceps muscle weakness influences the gait pattern in women with knee osteoarthritis - Spinoso, Deborah Hebling [UNESP]; Bellei, Natane Ceccatto [UNESP]; Marques, Nise Ribeiro; Navega, Marcelo Tavella [UNESP] (Springer Nature, 2018)
BACKGROUND: Osteoarthritis is the most prevalent rheumatic disease in the population and is characterized by limitation of main functional activities of daily living, as the gait. Muscle strength is a variable that may be related to performance in daily tasks.Therefore, we to analyze the gait pattern in individuals with knee osteoarthritis (KOA) and to determine associations of gait variables with the level of muscle strength of knee extensors. METHODS: Sixty-seven female volunteers divided into 2 groups, a KOA group (KOAG, n = 36, 66.69 ± 7.69 years) and control (n = 31, 63.68 ± 6.97 years), participated in the study. The volunteers walked on a 10-m platform at their usual gait speed, using 2 pressure sensors positioned at the base of the hallux and calcaneus. The mean step time, support and double support times, swing time and gait speed were calculated. The evaluation of the quadriceps isometric torque was performed in an extensor chair, with hip and knee flexion at 90°. The procedure consisted of three maximal contractions of knee extension. Peak torque was determined by the highest torque value obtained after the onset of muscle contraction. For statistical analysis, one-way ANOVA and Pearson's correlation were used, with p <  0.05. RESULTS: The KOAG had a 54.76% longer support time, a 13% longer step time (p <  0.001), a 30% decrease in swing time (p <  0.001) and a 10.7% decrease in gait speed (p = 0.001) compared with controls. The quadriceps isometric torque was 34% (p = 0.001) lower in the KOAG. There was a correlation between kinematic variables and quadriceps torque. CONCLUSION: Weakness of the quadriceps muscle in women with KOA influences gait pattern, resulting in reduced speed associated with a shorter swing time and longer support time.
Keywords: Falls; Kinematics; Torque